Para‐Selective Palladium‐Catalyzed C−H Difluoroalkylation by Weak Oxazolidinone Assistance. Issue 7 (24th February 2021) - Fang, Xinyue; Tan, Yuqiang; Gu, Linghui; Ackermann, Lutz; Ma, Wenbo
Abstract: Herein, we report a general and efficient method for the palladium‐catalyzed remote C(sp 2 )−H difluoroalkylation of N ‐aryloxazolidinone derivatives with commercially available difluoroalkyl bromide. This method tolerates a wide range of functional groups with 26 examples in up to 96 % yields. Moreover, it proceeds with complete para ‐selectivity. Preliminary mechanistic studies indicated that a single electron transfer process likely involved in this transformation. Abstract : Di‐amonds are forever : A general and efficient method for palladium‐catalyzed remote C(sp 2 )‐H difluoroalkylation of N ‐aryloxazolidinone derivatives with commercially available difluoroalkyl bromide have been developed.